A Rare Involvement of Left Main Coronary Artery Due to Woven Coronary Artery in a Patient with Behçet’s Disease - Tatar, Sefa; Alsancak, Yakup; Gürbüz, Ahmet Seyfeddin; İçli, Abdullah (European Journal of Therapeutics, 2023)
In general, woven coronary artery (WCA) is a benign congenital pathology; occasionally, it may result in adverse cardiovascular events owing to myocardial ischemia. Though all coronary arteries may be affected, the right coronary artery is the most affected. This paper presents an extremely rare WCA effecting the left main coronary artery concurrent with Behçet’s disease.